ANALISIS DAMPAK COVID-19 TERHADAP NILAI PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI - Ofeser, Fajri; Susbiyantoro, Susbiyantoro (POLITEKNIK LP3I JAKARTA, 2021)
This study examines the impact of Covid-19 on the firm value in the consumer goods industry sector. This study aims to determine whether there is a significant difference in the firm value of the consumer goods sector between before the Covid-19 pandemic and afterwards. The study used the average firm value in the consumer goods industry four months before the pandemic and four months after the discovery of the Covid-19 case in Indonesia. Sampling using purposive sampling with a sample size of 31 companies which are grouped into four sub-sectors. The study will examine the impact of Covid-19 on the consumer goods industry sector as a whole, as well as partially on each subsector. The data were tested by using the paired sample t-test method. The results showed that there was no significant difference in the company value of the consumer goods industry before and after the Covid-19 case. The results of the partial analysis of each subsector show that the cosmetic and house hold sub- sector and the food and beverage sub-sector have significant differences between before and after the pandemic, while the tobacco manufacturer and pharmaceutical sub-sectors have no significant differences in company value between before and after the pandemic.Key words: Impact of Covid-19, Firm Value, Consumer Goods